Qualidade motivacional para a profissionalidade docente na educação superior - Barros, Lívia de Melo (2016)
Motivation in the educational field has been a consolidated topic by several studies. However, specifically on teaching motivation, we can observe the bibliographical research, that there are very few studies that approach such a topic. Therefore, the teaching motivation is regarded an emerging topic that passes by the motivation on Education. It is ascribed to the professor the duty of motivating the students as well as the effectiveness of the teaching and learning process. Studies many times ignore the aspects which motivate the professor. Thats why, the current thesis had as a general goal to spot motivational aspects and how they impact both the motivational quality and professional level of the teachers of a private institution in the northeast of Brazil. Having as specific goals: verify how motivational aspects interfere in the professional level of the teacher; analyse emerging motivational aspects and the impact in the motivational quality since the continuum of the Theory of Self-determination; connect the sex and the time in the teaching with motivational aspects and professional level of college students. In order to do that, we have used the qualitative method, for data collection we have applied a social-demographical quiz and narrative interviews, with twelve professors of a private college, the sample has been defined by saturation. Narrated interviews have been fully transcribed and analysed by the Discourse Textual Analysis (MORAES; GALIAZZI, 2007). Results have been divided in four categories: personal aspects (the job persistence, passion for teaching, vanity protagonist- professor, curiosity, power investiment (gas)); interpersonal relationships (students, managers and workmates Relationships); professional levels principles (social commitment, people formation, professional development) and contextual aspects (income, workload variation, overcrowded rooms and voice loss , physical limitation). These categories provide motivational aspects that interfere in the teaching professional level and that have been related to the motivational quality as far as teaching is concerned. Henceforth we have identified that men have a higher persistence and connection to teaching, whereas women have a discourse that they are intrinsically motivated, but women have lower persistence in the classroom, once they intend to get into graduate stricto-sensu courses in order to reduce the workload in the classroom and have greater availability for research. Besides, during the results analysis “the research” has appeared as the goal and major motivation behind teaching, many professors are as professors, however they intend to be researches. This data has shown that despite the professor be framed by the tripod: teaching-research-extension, the interviewed teachers slightly realize these three characteristics related to the teaching professional level, only being the teaching or the research regarded as motivational aspects of the teaching , none of the interviewed professors who recognised the extension knew the extension as motivational aspect. As for the motivational quality, just an interview had a low motivational quality relating to the professional level quality, which had been ratified not only through the narrated interviewed as well as the abandonment of the professor to the teaching. Furthemore, we understand that it is not enough to know motivational aspects related to the professional teaching level, it is essential that this knowledge be translated in pedagogical practices that provide a better psychological well being both to the professors and students.